A conduit of grace: spirituality and social justice: A pastoral reflection - Pennington, Emma (Theology, 2024)
A pastoral reflection inspired by a prayer often attributed to St Theresa of Ávila, ‘Christ has no body but yours’. It recalls an occasion when a couple in need were found by the author sitting in her church porch.